2012
DOI: 10.1007/s13402-012-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Skewed immunological balance between Th17 (CD4+IL17A+) and Treg (CD4+CD25+FOXP3+) cells in human oral squamous cell carcinoma

Abstract: Our results suggest an increase in Th17/Tregs ratio in early stages and a decrease in this ratio in higher stages of oral cancer. Such counter regulation of Th17 and Tregs may be a significant prognostic factor in oral cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
3
43
2
1
Order By: Relevance
“…Taken together with previous studies investigating Treg cells in these tumors, 16,17 these findings corroborate the presence of this T cell subpopulation in the microenvironment of LLSCC. In the present study, 14 On the other hand, Gaur et al 12 observed a larger number of Treg cells in the peripheral blood of patients with oral SCC who had regional lymph node metastases and were in advanced clinical stages.…”
Section: 15mentioning
confidence: 40%
See 1 more Smart Citation
“…Taken together with previous studies investigating Treg cells in these tumors, 16,17 these findings corroborate the presence of this T cell subpopulation in the microenvironment of LLSCC. In the present study, 14 On the other hand, Gaur et al 12 observed a larger number of Treg cells in the peripheral blood of patients with oral SCC who had regional lymph node metastases and were in advanced clinical stages.…”
Section: 15mentioning
confidence: 40%
“…10 Several studies have associated a larger number of Treg cells in the tumor microenvironment with a reduced antitumor immune response and consequent poor prognosis. 6,11 In squamous cell carcinoma (SCC) of the oral cavity, a larger number of Treg cells have been associated with the presence of regional lymph node metastasis, 12 advanced clinical stage, 12 and low overall survival 13 and disease-free survival rates.…”
Section: 8mentioning
confidence: 99%
“…Furthermore, even established Th17 cells can be induced to produce IFN-γ in addition to IL17A (Th17/Th1 cells), suggesting a common developmental association between Th17 and at least a subset of Th1 cells (28). Notably, numerous studies have reported increased expression of IL17/Th17 cells in different cancers, including colorectal (29), prostate (30), gastric (31), lung (32), ovarian (33), oral (34) and head and neck (35) carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of immune surveillance is often observed in the early stage of OSCC [20]. However, the local and systemic cell-mediated response is suppressed following disease progression in cancer patients leading to the escape of tumor cells [21]. So far, the exact role of Tregs in the progression of OSCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%